Debate on Rice Import Policy in Indonesia: Discourse Network Analysis in Online Media - Haresti Asysy Amrihani; Eriyanto Eriyanto; Muhammad Yunus Zulkifli (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
This research maps the discourses on agreements and disagreements of each actor regarding the rice import policy in Indonesia. In 2023, the Indonesian government took a policy to increase the quota of rice imports Indonesia, according to the United States Department of Agriculture, is the worldâ€™s fifth largest country in terms of rice imports. The policy was opposed and supported by a number of actors since Indonesia is also the fourth largest rice producer in the world.Â  Actors who oppose and approve of the rice import policy in Indonesia present their respective arguments to influence the public. This research uses the Discourse Network Analysis (DNA) method to map the discourse coalition and actors based on the actors' arguments in Kompas.id media. The results show that the discourses of each actor are connected to each other. The discourses include: stabilizing rice reserves, international cooperation, reducing rice prices, anticipating climate change, importing rice during harvest, contradicting the food law, rising rice prices, rice stock alert, law enforcement against rice fraud, and rice procurement which is impossible.